Dynamic modelling and control an electric motorcycle for energy recovery via regenerative braking - Mohd Noor, Nurul Muthmainnah; Toha, Siti Fauziah; Abdullah, Muhammad; Ahmad, Salmiah (ASCEE, 2026)
The rapid expansion of the automobile industry, largely driven by population growth and urbanization, has intensi ied the demand for sustainable transportation solutions. In response, electric vehicles (EVs) have gained signi icant traction as cities strive to mitigate carbon emissions and improve energy ef iciency. This paper presents the development and modelling of an electric motorcycle system incorporating energy recovery mechanism to enhance overall energy ef iciency. The system was formulated using longitudinal vehicle dynamics equation and simulated in MATLAB to evaluate its performance. A regenerative braking system (RBS) was integrated into the model to investigate its effectiveness in energy recuperation, laying the groundwork for future advancements in electric motorcycle technology. Unlike conventional motorcycles, electric motorcycles leverage energy recovery to optimize performance and extend operational range. In this study, the World Motorcycle Test Cycle (WMTC) was selected as standardized drive cycles to assess the system’s response. The braking control was implemented using a Proportional-Integral controller to regulate braking force distribution effectively. Simulation results demonstrate that the integration of regenerative braking signi icantly enhances the state of charge (SOC), thereby extending the travel range. These indings highlight the potential further optimization through the implementing of advanced braking control strategies, contributing to the evolution of more ef icient and sustainable electric mobility solutions.